Pain control methods in use and perceived effectiveness by patients with Ehlers–Danlos syndrome: a descriptive study. Issue 11 (21st May 2016) - Arthur, Karen; Caldwell, Karen; Forehand, Samantha; Davis, Keith
Abstract: Purpose : The purpose of this study was to assess the pain control methods in use by patients who have Ehlers–Danlos Syndrome (EDS), a group of connective tissue disorders, and their perceived effectiveness. Method : This descriptive study involved 1179 adults diagnosed with EDS who completed an anonymous on-line survey. The survey consisted of demographics information, the Patient Reported Outcomes Measurement Information System (PROMIS) Pain-Behavior, PROMIS Pain-Interference, and Neuro QOL Satisfaction with Social Roles and Activities scales, as well as a modified version of the Pain Management Strategies Survey. Results : Respondents reported having to seek out confirmation of their EDS diagnosis with multiple healthcare providers, which implies the difficulty many people with EDS face when trying to gain access to appropriate treatment. Patients with EDS experience higher levels of pain interference and lower satisfaction with social roles and activities compared to national norms. Among the treatment modalities in this study, those perceived as most helpful for acute pain control were opioids, surgical interventions, splints and braces, avoidance of potentially dangerous activities and heat therapy. Chronic pain treatments rated as most helpful were opioids, splints or braces and surgical interventions. For methods used for both acute and chronic pain, those perceived as most helpful were opioids, massage therapies, splints or braces, heat therapy and avoiding potentially dangerous activities. Conclusions : EDS is a complex, multi-systemic condition that can be difficult to diagnose and poses challenges for healthcare practitioners who engage with EDS patients in holistic care. Improved healthcare provider knowledge of EDS is needed, and additional research on the co-occurring diagnoses with EDS may assist in comprehensive pain management for EDS patients. Implications for Rehabilitation: Ehlers–Danlos Syndrome (EDS) is a group of connective tissue disorders associated with defective production of collagen, which can dramatically reduce musculoskeletal functioning by symptoms of joint laxity and frequent dislocations eventually leading to disability. Respondents to an on-line survey reported having to seek out confirmation of their EDS diagnosis with multiple physicians, which implies the difficulty many people with EDS face when trying to gain access to appropriate treatment. Participants with EDS reported the most helpful methods for managing acute pain were opioids, surgical interventions, splints and braces, heat therapy, nerve blocks and physical therapy, while chronic pain was treated most effectively with opioids, heat therapy, splints or braces and surgical interventions.